The feminist case against pornography: a review and re-evaluation - Cawston A. (Inquiry (United Kingdom), 2019)
Despite sustained feminist criticism, the production and consumption of pornography does not show signs of waning. Here, I offer a critical review of the existing feminist anti-pornography debate, arguing that it has largely failed to provide suitable grounds for a stable and comprehensive critique, instead often indirectly providing theoretical resources for pornography to reinvent itself. This is a product, in my view, of a misguided focus on the pornographic object. Feminist critics are better served, I argue, by redirecting their critical gaze towards the consumers of pornography, and, in particular, to the attitudes such consumption reflects. To that end, I introduce an alternative, attitudinal approach that enables criticism of pornography as a reflection of sexist attitudes, as well as for its role in concealing these attitudes.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; cours; discipline; philosophie; philosophie politique; pornographie; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; santé; sciences humaines; sex1911; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; éthique

Biopolitique à l'ère du capitalisme pharmacopornographique - Preciado, Paul B. (Chimères, 2010)
Au cours de cette époque révolue, et pourtant récente, que nous appelons aujourd’hui fordisme, l’industrie de l’automobile synthétise et définit un mode spécifique de production et de consommation, une temporalisation tayloriste de la vie, esthétique polychrome et lisse de l’objet inanimé, une façon de penser l’espace intérieur et d’habiter la ville, un agencement conflictuel du corps et de la machine,...
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; biopolitique; cours; discipline; fem1000; philosophie politique; premier cycle; périodes historiques; queer; ressource en ligne; sciences humaines